Errors and difficulties in oral reading in Pilipino of grade two pupils in six elementary schools, Districts of Talisay, Division of Batangas - Landicho, Leovigildo B. 1919- (1969)
The purpose of the study is to make a critical analysis of the oral reading errors and difficulties in Pilipino of Grade Two pupils. At the same time, this is a pilot research in the field of oral reading in Pilipino which is the medium of instruction in Grades I and II. It aims to know the exact nature of the oral reading errors and difficulties in Pilipino and to suggest ways and means to correct them.
Vita.
Thesis (M. Ed.)--University of the Philippines, Diliman.
Keywords: Oral reading -- Philippines -- Talisay (Batangas); Reading (Elementary) -- Philippines -- Talisay (Batangas); Second grade (Education) -- Philippines -- Talisay (Batangas)